Acute and Chronic Pain Processing in the Thalamocortical System of Humans and Animal Models. (1st September 2018) - Groh, Alexander; Krieger, Patrik; Mease, Rebecca A.; Henderson, Luke
Highlights: Thalamocortical (TC) pathways encode sensory and emotional aspects of pain. The experience of pain arises from specific activity patterns in TC pathways. Chronic pain is linked to functional, anatomical and biochemical changes in TC pathways. Development of chronic pain treatments aim at altering neural and glial function. Abstract: The transmission of noxious stimuli from peripheral receptors to the cortex involves multiple central ascending pathways. While projections to areas in the brainstem and diencephalon are likely involved in mediating the immediate behavioral responses to pain, the assessment of the sensory and emotional/motivational components of pain are likely processed in parallel ascending pathways that relay in the thalamus on their way to the cerebral cortex. In this review we discuss experimental animal and human findings that support the view that a lateral thalamocortical pathway is involved in coding the sensory discriminative aspects of pain, while a medial thalamocortical pathway codes the emotional qualities of pain. In addition, we outline experimental animal and human evidence of functional, anatomical and biochemical alterations in thalamocortical circuits that may be responsible for altered thalamocortical rhythms and the persistent presence of pain following nervous system damage. Finally, we discuss advances in clinical and preclinical development of chronic pain treatments aimed at altering neural and glial function.